Brachionid Rotifers (Eurotatoria: Monogononta) from Meizailung Fish Farm, with Four Records in Ukhrul District, Manipur, India - Raihing, Vimi; Jajo, Ersilia; Mecadon, Hormi; Ngaomei, Gaikhuanlung; Ngalo, Mungrei; Rungsung, Shunringla; Sinha, Bikramjit (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from January to December, 2023 at Meizailung Fish Farm Ukhrul District, Manipur, India, to provide valuable taxonomic descriptions and highlight the Brachionid rotifer's ecological significance in freshwater habitats. Brachionid rotifers played a vital part in aquatic ecosystems, acting as primary consumers in freshwater habitats and significantly contributing to nutrient cycling and energy transfer. This study investigates the diversity and records of brachionid rotifers from Meizailung Fish Farm, Ukhrul District, Manipur, India. Monthly sampling was conducted, covering different seasons to assess seasonal variations in species composition and abundance. Water samples were collected using plankton nets (mesh size: 55 µm) and analyzed using standard taxonomic keys. Physicochemical parameters such as temperature, pH, dissolved oxygen, free carbon dioxide, alkalinity, Ammonium nitrate, phosphates, and chlorides were also measured to determine their influence on rotifer distribution. Out of 12 rotifer species belonging to the family Brachionidae (Eurotatoria: Monogononta), the genus Brachionus was the most abundant, with 8 species recorded. Among these, 4 species- Anuraeopsis ceolata, Anuraeopsis navicula, Brachionus budapestinensis, Keratella valga were state records from Manipur. The highest diversity was observed during the pre-monsoon season, while the lowest was recorded in winter. This study highlighted the rich biodiversity of brachionid rotifers in Meizailung Fish Farm, with four records contributing to the understanding of regional zooplankton diversity. These findings provide baseline data for the region's future ecological monitoring and aquaculture management. Further investigations on the functional role of rotifers in local aquatic food webs are recommended.